Cross-linguistic transfer and ambient phonology: impact on diagnosis of speech sound disorders in a longitudinal bilingual case study - Margetson, Kate; McLeod, Sharynne; Verdon, Sarah (Journal of Monolingual and Bilingual Speech, 2023)
For speech-language pathologists (SLPs) working with multilingual children, differential diagnosis between typical development and speech sound disorder may be complex. This paper presents a longitudinal case study of a bilingual Vietnamese–Australian child (PE) between the ages of 3 years;10 months (3;10) and 6;10, to explore the impact of cross-linguistic transfer and ambient phonology on speech acquisition. PE completed speech assessments as a participant in the VietSpeech Study: the Vietnamese Speech Assessment and the Diagnostic Evaluation of Articulation and Phonology in English. Differential diagnosis based on English speech assessment alone indicated speech sound disorder; yet differential diagnosis based on speech assessment in both languages revealed developmental, cross-linguistic transfer, and ambient phonological influences to be the primary reasons for mismatches. Independent and relational analyses at 3;10 revealed age-appropriate phonetic inventories in Vietnamese and English and bi-directional cross-linguistic transfer: segmental transfer of non-shared consonants, non-shared phonological patterns, and a preference for palatal and retroflex consonants. Contrastive analysis with family members demonstrated the impact of ambient phonology on PE’s speech. Over the three years her speech accuracy improved and mismatches reduced. By 6;10 her English speech was age appropriate and some cross-linguistic transfer was still evident in Vietnamese. Evidence is presented for how dual phonological systems can interact over time until they stabilize. During differential diagnosis, SLPs need to consider the influence of cross-linguistic transfer and ambient phonology on bilingual speech acquisition.